Safe needling of arteriovenous fistulae in patients on hemodialysis: Literature review and a new approach - Peralta, R.; Matos, J. M. de; Carvalho, H. (Nephrology Nursing Journal, 2021)
Although buttonhole cannulation has some benefits compared to rope-ladder cannulation, the increase of infection rates represents a major obstacle to patient safety, and its use is questionable in routine clinic practice. On the other hand, rope-ladder cannulation is difficult to implement even with a prescribed protocol, leading the cannulator in daily practice to a possible use of the area technique. This article provides a reflection on the impact of cannulation technique on the safety of patients on regular hemodialysis treatment and describes a new approach for arteriovenous fistula cannulation, the Multiple Single Cannulation Technique (MuST). The MuST has not been described before, but it has been used with promising results. Further studies are needed to confirm the benefits of this cannulation technique.